Update on integrative treatment of psychiatric symptoms and disorders in athletes. Issue 4 (1st October 2020) - Glick, Ira D.; Stillman, Mark A.; McDuff, David
ABSTRACT: Primary objective : In this review, we detail the issues and disorders athletes present with, guidelines for making diagnostic formulations and treatment goals, and strategies for delivering integrated treatment attuned to the athlete and their team and/or sport. In addition, we highlight special issues associated with athletes and their families. Reasoning : Data suggests athletes experience comprable incidence and prevalence rates to the general population of psychiatric disorders. The mental and physical demands placed on athletes are unique and may increase their susceptibility to certain mental health problems. The current literature regarding integrative interventions in athletes is sparse and largely anecdotal. We provide a summary of the scientific evidence from a literature review conducted by the IOC Consensus Committee on Mental Health in Elite Athletes, reviews and expert clinical strategies recommended by the authors of four books on sports psychiatry written since 2012, and our own review of the literature related to psychotherapy with elite and non-elite- athletes. Main outcomes and results : At the moment there are no randomized controlled trials assessing the use of psychotherapy or medication for mental illness in athletes to guide treatment. Controlled studies examining psychological interventions in collegiate athletes have demonstrated improvements in mental health symptomology. Although these studies were limited to collegiate athletes they assist in providing a foundation for elite athletes as well. For the assessment and management of the mental health needs of athletes' to be on a par with their physical needs, more high-quality scientific epidemiological and treatment intervention studies are needed. Conclusions : Development of specific models of psychiatric intervention for athletes with significant psychopathology and impairment appears to be warranted. These interventions should include individual, family/marital, and group psychotherapy with or without medication using evidence-based treatments.